THE INFLUENCE OF WORK DISCIPLINE, MOTIVATION, ORGANISATIONAL CLIMATE AND WORK SATISFACTION OF JAYAPURA CITY EDUCATIONAL OFFICE PERSONALS - Nurlina Mane; Duta Mustajab (Journal of Economics Review (JOER), 2022)
This study is aimed to determine work discipline, motivation, organizational climate and work satisfaction on the performance of the Jayapura city educational office personals. Samples were taken using saturated sampling method with a total sample of 79 respondents. The analytical method used is multiple linear regression. The results show that that the work discipline had a negative and significant effect on the performance of the Jayapura city educational office personals. Motivation has no effect and is not significant on the performance of the Jayapura city education office personals. organizational climate and job satisfaction have a positive and significant effect on the performance of Jayapura education office personals